2015
DOI: 10.1159/000381549
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neurokinin-1 Receptors Contribute to Kaolin-Induced Acute Monoarthritis in Rats

Abstract: Objective: intra-articular co-injection of kaolin with carrageenan (CGN) in rodents is widely used as an experimental model of arthritis. However, the ability of kaolin to cause arthritis and related immune responses when administered alone is unclear. We evaluated the contribution of prostanoids and sensory C-fibres (and their neuropeptide substance P) to kaolin-induced inflammation in the rat knee. Methods: Wistar rats, 8-10 weeks old, received an intra-articular injection of kaolin (1-10 μg/joint) or saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The kaolin induced inflammation model lead to the increase of proinflammatory cytokines e.g. f IL-1β, IL-6 and TNFα [ 55 ]. Studies showed that flavonoids [ 56 , 57 ] and quercitin [ 58 , 59 ] downregulates the expression of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The kaolin induced inflammation model lead to the increase of proinflammatory cytokines e.g. f IL-1β, IL-6 and TNFα [ 55 ]. Studies showed that flavonoids [ 56 , 57 ] and quercitin [ 58 , 59 ] downregulates the expression of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that administration of NK1 receptor antagonists decrease pain sensation in rats with induced monoarthritis [176, 177]. Uematsu et al [176] induced inflammation in rats, then conducted histological analysis of rodent cartilage.…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…Research suggests that pain transmission pathways may play a significant role in this process. For example, neurokinin has been shown to both decrease inflammatory pain and joint cartilage destruction in rats [176, 177]. Preventing joint destruction in this case may also prevent osteoarthritis-related pain.…”
Section: Five-year Viewmentioning
confidence: 99%